Uniaxial Compression Damage Mechanical Properties and Mechanisms of Dolomite Under Deep High-Humidity Condition - Chen, Wei; Peng, Wenqing; Wan, Wen; Wang, Xianqing; Wu, Qiuhong; Zhou, Yu; Xie, Senlin (Frontiers in Materials, 2022)
The paper studies the uniaxial compression mechanical properties of pillars under the deep and high-humidity environment. We make the pillars cored from the −750 m mine room of Wengfu Phosphate Mine into the standard dolomite samples and test with a humidity control device developed by ourselves. Combining with uniaxial compression tests and microstructure inspections, we study the mechanical deterioration rule and damage mechanism of the dry samples and the wet ones that have been placed in a high-humidity condition (90% RH) for 30, 60 and 90 d, respectively. The results show that: 1) When the sample is placed in the humidity device, its original layered or sheet crystal morphology will change into sponge-like or flocculent morphology. As the placement time increases, the structure of the sample becomes looser and the boundaries between layers become blurred. The numbers of micro-cracks and micro-pores increase. 2) In the initial stage of water molecule intrusion (0–30 d), the strength and mass damages of the rock sample are less, and the damage rate is low. As high-humidity action time increases (30–90 d), the damage rates of both strength and mass gradually grow. 3) The failure modes of dolomites include shear failure and tensile/shear mixed failure, which are controlled by the storage time under high-humidity condition. As time goes by, more macroscopic cracks appear and the failure mode of the rock changes from shear to tensile. 4) Based on the X-ray diffraction and scanning electron microscopy analysis on mineral components, together with the principle of chemical kinetics, we discuss the chemical reaction process between dolomite and gaseous water molecules, and summarize the chemical damage mechanism of rocks during the water-rock interaction. The research has a certain guiding significance for the durability and stability prediction of pillars under deep high-humidity conditions.